Cost-effectiveness analysis of pembrolizumab versus targeted therapies in advanced melanoma - E. G. Kosolapov; F. S. Kochenkov; S. K. Zyryanov; O. A. Gladkov (Izdatelstvo OKI, 2018)
Background. The modern therapies of advanced melanoma include targeted medicines for patients with BRAF mutations. Nowadays, a new perspective on immuno-oncologic medicine pembolizumab became available in Russia. Objective. Assessment of the clinical and economic effectiveness of the use of pembolizumab in the treatment of unrespectable and metastatic melanoma in comparison with targeted medicines in the context of Russian public health. Materials and methods. The Markov model was developed, including the states «without progression», «after progression» and «death», the duration of one Markov cycle is 1 month, the modeling time horizon is 5 years. The probabilities of transitions between states were described using mathematical formulas obtained as a result of digitization and approximation of Kaplan-Mayer survival curves, which were derived from randomized clinical trials KEYNOTE-006, COMBI-v and COMBI-d. Direct medical costs (including drug costs, treatment of adverse events, second-line therapy after disease progression, and palliative care) were analyzed. We did not take into account the costs associated with laboratory-diagnostic procedures and visits to the doctor. The sources of information were: weighted average prices of medicines indicated during public procurement for 2016 (the price of the drug pembolizumab provided by the manufacturer), a program of state guarantees for providing free medical care to Russian citizens for 2016, federal coefficients of relative costs for clinical and statistical groups. The effectiveness criterion for cost-effectiveness analysis was the average number of saved months of a patient's life. Results. The average number of months saved was 30, 23, 24 and 30 months with pembolizumab, vemurafenib, dabrafenib and dabrafenib plus tramethanib, respectively (calculated using the developed model). Thus, pembolizumab has the same effectiveness as a combination of dabrafenib + tramethanib and is more effective than monotherapy with targeted drugs (dabrafenib or vemurafenib). Direct medical costs per patient over 5 years were approximately 4.06, 5.53, 5.91 and 15.72 million rubles when using pembolizumab, dabrafenib, vemurafenib and a combination of dabrafenib + trametinib, respectively. The health budget saving with pembolizumab instead of dabrafenib, vemurafenib and dabrafenib + trametinib combination may be 26%, 31% and 74%, respectively. Conclusion. Pembolizumab is a rational and economically justified choice for the treatment of unresectable and metastatic melanoma since it leads to cost savings when overall survival is increased.